Sex- and tissue-specific expression of chemosensory receptor genes in a hawkmoth - Tom, Megha Treesa; Cortés Llorca, Lucas; Bucks, Sascha; Bisch-Knaden, Sonja; Hansson, Bill S. (Frontiers in Ecology and Evolution, 2022)
For the nocturnal hawkmoth Manduca sexta, olfactory and gustatory cues are essential for finding partners, food, and oviposition sites. Three chemosensory receptor families, odorant receptors (ORs), ionotropic receptors (IRs) and gustatory receptors (GRs) are involved in the detection of these stimuli. While many chemosensory receptor genes have been identified, knowledge of their expression profile in potentially chemoreceptive organs is incomplete. Here, we studied the expression patterns of chemosensory receptors in different tissues including the antennae, labial palps, proboscis, legs, wings and ovipositor. We compared the receptors’ expression in female and male moths both before and after mating by using the NanoString platform. This tool allowed us to measure expression levels of chemosensory receptor genes in a single reaction using probes designed against 71 OR, 29 IR and 49 GR transcripts. In all tissues investigated, we detected expression of genes from all three receptor families. The highest number of receptors was detected in the antennae (92), followed by the ovipositor (59), while the least number was detected in the hindlegs (21). The highest number of OR genes were expressed in the antennae (63), of which 24 were specific to this main olfactory organ. The highest number of IRs were also expressed in the antennae (16), followed by the ovipositor (15). Likewise, antennae and ovipositor expressed the highest number of GRs (13 and 14). Expression of the OR co-receptor MsexORCo, presumably a prerequisite for OR function, was found in the antennae, labial palps, forelegs and ovipositor. IR co-receptors MsexIR25a and MsexIR76b were expressed across all tested tissues, while expression of the IR co-receptor MsexIR8a was restricted to antennae and ovipositor. Comparing the levels of all 149 transcripts across the nine tested tissues allowed us to identify sex-biased gene expression in the antennae and the legs, two appendages that are also morphologically different between the sexes. However, none of the chemosensory receptors was differentially expressed based on the moths’ mating state. The observed gene expression patterns form a strong base for the functional characterization of chemosensory receptors and the understanding of olfaction and gustation at the molecular level in M. sexta.